2017
DOI: 10.2215/cjn.11941116
|View full text |Cite
|
Sign up to set email alerts
|

Renal Functional Outcomes after Surgery, Ablation, and Active Surveillance of Localized Renal Tumors: A Systematic Review and Meta-Analysis

Abstract: Renal functional implications varied across management strategies for localized renal masses, with worse postoperative renal function for patients undergoing radical nephrectomy compared with other strategies and similar outcomes for partial nephrectomy and thermal ablation. Further attention is needed to quantify the changes in renal function associated with active surveillance and nephron-sparing approaches for patients with preexisting CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(65 citation statements)
references
References 71 publications
3
61
0
1
Order By: Relevance
“…In the meta‐analysis, no differences in renal function were found between PN and ablation patients, but data were insufficient to compare either intervention against the AS group . Results from the present study corroborate these retrospective findings in a prospective cohort but also provide insight into direct comparisons of renal function to AS, which was previously found not to preserve eGFR any better than PN or ablation .…”
Section: Discussionsupporting
confidence: 64%
“…In the meta‐analysis, no differences in renal function were found between PN and ablation patients, but data were insufficient to compare either intervention against the AS group . Results from the present study corroborate these retrospective findings in a prospective cohort but also provide insight into direct comparisons of renal function to AS, which was previously found not to preserve eGFR any better than PN or ablation .…”
Section: Discussionsupporting
confidence: 64%
“…Renal dysfunction after thermal ablation is proportional to the greatest tumor dimension and the volume of ablation zones, with most ablated tumors in the literature ranging in size from 2 to 3 cm in greatest dimension. In a recent systematic review and meta‐analysis of 18 studies comparing changes in eGFR after partial nephrectomy versus thermal ablation for small renal masses, mean GFR losses of −6.2 mL per minute and −4.5 mL per minute, respectively, were observed for each modality . The results from the current cohort of patients who received SABR for T1a disease are comparable (−4.0 mL per minute) to these other modalities, although many patients had pre‐existing renal dysfunction.…”
Section: Discussionmentioning
confidence: 63%
“…One important aspect, which was not a prespecified aim of this review, was evaluating the minimum follow-up time for outcome reporting. In a recent systematic review, Patel et al [61] reported that a level of functional recovery could be expected after 6 mo following nephrectomy, and in a recent population-based study of 14 129 American patients, Leppert et al [62] found that the median time to stage 4 or higher CKD was 5 mo after nephrectomy, with 75% of events occurring within 9 mo. In the absence of more robust data, it is reasonable to consider 6 mo as a minimum time to followup when evaluating absolute postoperative eGFR in nephrectomy patients, and 9 mo when considering postoperative CKD.…”
Section: Discussionmentioning
confidence: 99%